An Overview of Soil Models for Earthquake Response Analysis - Yunita, Halida; Hendriyawan, H.; Apriadi, Dedi (Journal of Engineering and Technological Sciences, 2015)
Earthquakes can damage thousands of buildings and infrastructure as well as cause the loss of thousands of lives. During an earthquake, the damage to buildings is mostly caused by the effect of local soil conditions. Depending on the soil type, the earthquake waves propagating from the epicenter to the ground surface will result in various behaviors of the soil. Several studies have been conducted to accurately obtain the soil response during an earthquake. The soil model used must be able to characterize the stress-strain behavior of the soil during the earthquake. This paper compares equivalent linear and nonlinear soil model responses. Analysis was performed on two soil types, Site Class D and Site Class E. An equivalent linear soil model leads to a constant value of shear modulus, while in a nonlinear soil model, the shear modulus changes constantly,depending on the stress level, and shows inelastic behavior. The results from a comparison of  both soil  models  are  displayed in the form of maximum acceleration profiles and stress-strain curves.